The impact of ECB banking supervision on climate risk and sustainable finance - Lena Schreiner; Andreas Beyer (European Central Bank (ECB), 2024)
This paper provides a first empirical analysis of the impact of the European Central Bank's (ECB's) climate-risk-related supervisory efforts on (i) climate risk exposure and related risk management of banks; and (ii) on the induced shifts in banks' portfolio choices with regard to additional green finance. From 2020 onwards, the ECB has introduced various measures to enhance climate-risk-related supervisory efforts. Our identification strategy exploits the fact that the ECB's efforts on climate supervision has only been introduced for selected banks within the European Union i.e., the Significant Institutions under the Single Supervisory Mechanism. Other banks (i.e., the Less Significant Institutions) have remained unaffected. We set up a difference-in-difference setup based on a novel data set and find a significant impact on both improvements in climate risk exposure and management and on an increase in banks' green finance activities.
Keywords: D25; G21; G28; 330; Banking Supervision; Climate Stress Test; Green Lending; Sustainable Finance